2017
DOI: 10.1017/s0033291717001222
|View full text |Cite
|
Sign up to set email alerts
|

Acute memory and psychotomimetic effects of cannabis and tobacco both ‘joint’ and individually: a placebo-controlled trial

Abstract: BackgroundCannabis and tobacco have contrasting cognitive effects. Smoking cannabis with tobacco is prevalent in many countries and although this may well influence cognitive and mental health outcomes, the possibility has rarely been investigated in human experimental psychopharmacological research.MethodThe individual and interactive effects of cannabis and tobacco were evaluated in 24 non-dependent cannabis and tobacco smokers in a randomized, placebo-controlled, double-blind, 2 (cannabis, placebo) × 2 (tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 69 publications
1
76
0
Order By: Relevance
“…Anxiety was assessed with the State–Trait Anxiety Inventory (STAI) and depression with the Beck Depression Inventory (BDI) . A comprehensive drug history was taken . Pre‐morbid verbal intelligence was indexed by the Spot the Word task .…”
Section: Methodsmentioning
confidence: 99%
“…Anxiety was assessed with the State–Trait Anxiety Inventory (STAI) and depression with the Beck Depression Inventory (BDI) . A comprehensive drug history was taken . Pre‐morbid verbal intelligence was indexed by the Spot the Word task .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, and similar to other studies [33][34][35][36], participants were excluded if they: Self-reported as a daily smoker [37,38] Self-reported being pregnant [39] Exercised within 5 hours of testing [40] Consumed caffeine within 3 hours of testing [41] Had a concussion or head trauma within the past 30 days [42] Took marijuana or other illegal drugs within the past 30 days [43] Were considered a daily alcohol user (>30 drinks/month for women; >60 drinks/month for men) [44]…”
Section: Participantsmentioning
confidence: 99%
“…Similar to other studies [13], participants were excluded if they: Self-reported as a daily smoker [14,15] Self-reported being pregnant [16] Exercised within 5 hours of testing [17] Consumed caffeine within 3 hours of testing [18] Had a concussion or head trauma within the past 30 days [19] Took marijuana or other illegal drugs within the past 30 days [20] Were considered a daily alcohol user (>30 drinks/month for women; >60 drinks/month for men) [21]…”
Section: Participantsmentioning
confidence: 99%